Melatonin as a regulator of plant ionic homeostasis: implications for abiotic stress tolerance. (30th May 2022) - Huang, Xin; Tanveer, Mohsin; Min, Yu; Shabala, Sergey
Abstract : Melatonin controls intracellular ion homeostasis by regulating H + -ATPase activity, ROS–Ca 2+ hub operation, and hormonal cross-talks, which enable plant adaptation to hostile environmental conditions. Abstract: Melatonin is a highly conserved and ubiquitous molecule that operates upstream of a broad array of receptors in animal systems. Since melatonin was discovered in plants in 1995, hundreds of papers have been published revealing its role in plant growth, development, and adaptive responses to the environment. This paper summarizes the current state of knowledge of melatonin's involvement in regulating plant ion homeostasis and abiotic stress tolerance. The major topics covered here are: (i) melatonin's control of H + -ATPase activity and its implication for plant adaptive responses to various abiotic stresses; (ii) regulation of the reactive oxygen species (ROS)–Ca 2+ hub by melatonin and its role in stress signaling; and (iii) melatonin's regulation of ionic homeostasis via hormonal cross-talk. We also show that the properties of the melatonin molecule allow its direct scavenging of ROS, thus preventing negative effects of ROS-induced activation of ion channels. The above 'desensitization' may play a critical role in preventing stress-induced K + loss from the cytosol as well as maintaining basic levels of cytosolic Ca 2+ required for optimal cell operation. Future studies should focus on revealing the molecular identity of transporters that could be directly regulated by melatonin and providing a bioinformatic analysis of evolutionary aspects of melatonin sensing and signaling.